Condors, Water, and Mining: Heeding Voices from Andean Communities - Sault, Nicole (Ethnobiology Letters, 2018)
This paper addresses the relationship between scholarship and activism, considering the obligations that ethnobiologists have to the communities we work with. I begin by describing the cultural meaning of Andean condors (Vultur gryphus) in Peru through their connections to mountains and water in various forms, and the condor’s role as guardian and protector. My research on condors led me to Indigenous beliefs and practices regarding sacred mountains and water, and from this to the threats against the environment posed by international mining operations. This discussion highlights questions concerning the scholar’s role in situations of environmental destruction and political conflict in relation to structural violence, the mass media, and climate change. At a time when those who protect the land and water are endangered around the globe, the decisions we make while conducting research carry responsibilities for the consequences of our actions, even as these consequences ripple out beyond our specific locality and our original intentions.